PENGARUH SHARED VALUE, CONSUMER KNOWLEDGE DAN COMMUNICATION TERHADAP MINAT NASABAH PADA PERBANKAN SYARIAH (STUDI PADA DOSEN DAN TENAGA KEPENDIDIKAN DI IAIN KENDARI DAN UNIVERSITAS MUHAMMADIYAH KENDARI) - Muhamad Turmudi (Institut Agama Islam Negeri Kendari, 2019)
The growth of syariah’s banking customers under conventional banks is a result of the public's perception that the Islamic banking system as if the conventional system which only changed its name to syari'ah had an effect on people's interest in becoming customers. Therefore, it is necessary to know how many variables that affect the interest to become customers in Islamic banks. This research was quantitative by using multiple linear regression analysis methods to determine the influence of shared value, consumer knowledge, and communication partially and simultaneously to the interest of a customer. Simultaneously through the F-test variables X1, X2 and X3 had a significant influence on Y based on the F-count greater than the value of F-table of 2.7 (24.504>2.7) and the significance value F of 0.000 was smaller than the significant value of 0.05 (0,000<0,05). However, partially through the T-Test which had a significant effect on the interest in becoming a customer was X2 with a t-count value of 4.294 and a significant level of t equal to 0,000 smaller than α=5% (Sig.<0.05) and X3 with a value t-count is 2.475 and the level of significance t is 0.016 smaller than α = 5% (Sig.<0.05). While X1 did not have a significant effect because the value of t-count is -0.932 with a significant level of t of 0.355 greater than α = 5% (Sig.>0.05). The contribution value of the influence of X1, X2, and X3 on Y is 52.3% based on the test results of the coefficient of determination which had the value of R-Square (R2) of 0.523.